STUDENTS' ABILITY TO ANALYZE INTERPERSONAL MEANING THROUGH MOOD SYSTEM IN ENGLISH TEXTS - Yen Aryni; Lis Supiatman; Ananda Khumairoh; Wulan Sari (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
The purpose of this study was to assess the students’ ability to analyze interpersonal meaning through the Mood System in English text. The study used a qualitative descriptive design. The participants of this study were 20 students of English Education Study Programmed of Universitas Asahan who had acquired Systemic Functional Linguistics especially in interpersonal meaning and analysis of Mood System. The data were acquired by means of a written test in which students were asked to analyze five clauses selected from English texts. The analysis was in four parts: identifying Subject, identifying Finite, finding forms of Mood and distinguishing Mood and Residue structures. Data were analyzed descriptively by data collection, data reduction, data display and conclusion drawing. The findings showed that the students performed well to exceptional in analyzing interpersonal meaning through the Mood System. The students scored 86% in identifying Subject, 84% in identifying Finite, 100% in identifying Mood kinds and 88% in differentiating Mood and Residue structures. The findings also showed that the most challenging thing that students found to recognized was Finite since many students got confused with Finite and Predicator in verbal groups. In conclusion, the results suggest that the students were able to comprehend the communicative roles that are expressed by Mood structures in English clauses. The present study reveals the effectiveness of Mood System analysis in assisting students to comprehend interpersonal meaning and enhance their discourse analysis competency in English language acquisition